A Sub-Threshold Microwave RFID Tag Chip, Compatible With RFID MIMO Reader Technology - Haddadian, Sanaz; Scheytt, J. Christoph; von Bögel, Gerd; Grenter, Thorben (IEEE Journal of Radio Frequency Identification)
We present a fully integrated radio frequency identifications transponder chip operating at 5.8 GHz, which is compatible with the class-1 generation-2 of the Electronic Product Code protocol (EPC-C1 G2). The tag chip including the analog front-end and the digital baseband processor, are designed in the sub-threshold regime (0.5 V) with a total supply current of less than 50 μA. As a power scavenging unit, a single-stage differential-drive rectifier structure is designed and fabricated with standard threshold voltage (SVT) MOS elements in a commercial 65-nm CMOS process, to provide 0.8 V of rectified voltage. Measurements performed on the fabricated single-stage structure show a maximum power conversion efficiency of 69.6% for a 22 kΩ load and a sensitivity of -12.5 dBm, which corresponds to more than 1 m of reading range. The power conversion efficiency at this range is about 64%.

Analysis, Design and Implementation of a Fully Integrated Analog Front-End for Microwave RFIDs at 5.8 GHz to be Used with Compact MIMO Readers - Haddadian, Sanaz; Scheytt, Christoph (IEEE Journal of Radio Frequency Identification)
In this paper we present the system and circuit level analysis and feasibility study of applying microwave Radio Frequency Identification (RFID) systems with multipleinput multiple-output (MIMO) reader technology for tracking machining tools in multipath fading conditions of production environments. In the proposed system the MIMO reader interrogates single-antenna tags, and a high RFID frequency of 5.8 GHz is chosen to reduce the size of the reader's antenna array. According to the requirements dictated by the performed system analysis at 5.8 GHz, a low power fully integrated analog frontend (AFE) is designed and fabricated in a standard 65-nm CMOS technology for low power passive transponders. Performance of the Differential Drive Rectifier (DDR) topology as the core of the energy harvesting unit is investigated in detail. A multi-stage DDR power scavenging unit is dimensioned to provide a 1.2 V rectified voltage for 20-30 kQ load range, with a high power conversion efficiency (PCE) for high frequency and low input power level signals. The rectified voltage is then converted to a 1 V regulated voltage for the AFE and the baseband processor with 30 to 50 μW of estimated power consumption. Transistors with standard threshold voltage (VT) have been used for implementation. Measurements of the fabricated multi-stage configuration of the circuit show a maximum PCE of 68.8% at -12.46 dBm, and an input quality factor (Q-factor) of approximately 10. Amplitude-shift keying (ASK) demodulator and backscattering modulator with 80% modulation index, operating according to EPC-C1G2 protocol are applied for data transfer. The AFE consumes less than 1 μW in the reading mode. The AFE tag chip is 0.55 × 0.58 mm 2 .

A 5.8 GHz CMOS Analog Front-End Targeting RF Energy Harvesting for Microwave RFIDs with MIMO Reader - Haddadian, Sanaz; Scheytt, Christoph (IEEE International Conference on RFID Technology & Application (RFID-TA))
Targeting the feasible application of microwave RFID systems with MIMO reader technology for tracking small objects in multipath fading conditions, we present a fully integrated Analog Front-End (AFE) designed and fabricated in a standard 65-nm CMOS technology for low power passive RFID tags in the 5.8 GHz ISM band. A differential drive power scavenging unit is dimensioned to provide a 1.2 V rectified voltage resulting in a 1 V regulated voltage for the AFE while supplying a 50 μW load. Transistors with standard threshold voltage (V th ) have been used for implementation. Measurements of the fabricated circuits show a maximum Power Conversion Efficiency (PCE) of 71.8% at -12.5 dBm, and an input quality factor (Q-factor) of approximately 10.

Wireless Energy Harvesting in RFID Applications at 5.8 GHz ISM Band, a System Analysis - Haddadian, Sanaz; Scheytt, Christoph (Electromagnetics Research Symposium)
A complete system analysis for an integrated passive RFID transponder designed at 5.8 GHz range is presented, and a comprehensive set of design concerns for the rectifier circuit as the core of the harvesting block is also discussed. The system analysis is complemented by transistor-level design and simulation of harvesting circuits in a commercial 65 nm CMOS technology. A differential drive rectifier (DDR) has been selected as the most efficient harvesting topology for microwave frequency applications, which works at very low input power levels. The circuit was designed and simulated including chip layout parasitics and antenna matching circuitry. Considering the power budget of the tag chip, a power conversion efficiency of roughly 68.4% is achieved in simulation for an input RF power of around -11.26dBm.

SHF RFID System for Automatic Process Optimization with Intelligent Tools - Kuhn, Peter; Haddadian, Sanaz; Meyer, Frederic; Hoffmann, Marc; Grabmaier, Anton; Scheytt, Christoph; Kaiser, Thomas (Smart SysTech 2017; European Conference on Smart Objects, Systems and Technologies)
In this paper we present theoretical, simulated and measured data for a reader to tag communication RFID system at 5.8 GHz. First a theoretical link budget analysis for a reader to tag architecture is shown for a wireless industrial application at 1m distance. This includes a power budget of the passively powered transponder. The received power level of the backscattered data for the theoretical link budget is -52:5 dBm. For the first setup slot antennas are developed and measured in the anechoic chamber. The measured gain is 4.0 dB. The power of the backscatter data in setup 1 is -74:8 dBm. This corresponds to the theoretical link budget since, all losses such as cable or lower antenna gain are taken into account. Setup 2 is upgraded on the reader side with horn antennas. At 5.8 GHz, the gain reaches the value of 10.8 dB. The second setup shows improvement in the receiving backscattered power to a value of -62:4 dBm. Furthermore, as a solution to detect those transponders not presented in the main slope of the antenna, a steerable beam is introduced by means of a Rotman lens. On the topic of the passive transponder, different harvesting topologies at 5.8 GHz are investigated, and the efficiency simulation of the harvesting circuitry has been performed. The simulated efficiency of the implemented technique is 68 %.